A Critical Review of the Book Views on Economic Psychology - S.M. Reza Amiri Tehrani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2022)
This article aims at reviewing Tamaddon’s idea about economic psychology, which is presented in his book titled as "Views on Economic Psychology". Firstly, the role of psychologism in the history of science and its relevance to philosophy, humanities, and social sciences is introduced. This is to say that, psychologism in Britain, utilitarianism, psychologism in Germany and the Austrian school of economics are reviewed. British psychologism which believes in universal scientific laws abstracted from experiences in order to explain human behavior, is crystallized in methodological individualism and rationalism. German psychologism in its historical approach is to understand and describe human behavior. The Austrian school of economics is somewhere between these two schools of psychologism, meaning that while it recognizes social and cultural entities, it is also indebted to methodological individualism. John Maynard Keynes introduces the concept of animal spirit and shows its impacts on individual behaviors and suggests the economic psychology of a society of individuals based on conventions. Secondly, the economic psychologism ideal of Tamaddon and its relevance to philosophical and economic thoughts, especially to that of John Maynard Keynes’ attitude is surveyed. This article is based on descriptive and analytical methodology.